Oxidative Stress in Cell Death and Cardiovascular Diseases. (4th November 2019) - Xu, Tao; Ding, Wei; Ji, Xiaoyu; Ao, Xiang; Liu, Ying; Yu, Wanpeng; Wang, Jianxun
Abstract : ROS functions as a second messenger and modulates multiple signaling pathways under the physiological conditions. However, excessive intracellular ROS causes damage to the molecular components of the cell, which promotes the pathogenesis of various human diseases. Cardiovascular diseases are serious threats to human health with extremely high rates of morbidity and mortality. Dysregulation of cell death promotes the pathogenesis of cardiovascular diseases and is the clinical target during the disease treatment. Numerous studies show that ROS production is closely linked to the cell death process and promotes the occurrence and development of the cardiovascular diseases. In this review, we summarize the regulation of intracellular ROS, the roles of ROS played in the development of cardiovascular diseases, and the programmed cell death induced by intracellular ROS. We also focus on anti-ROS system and the potential application of anti-ROS strategy in the treatment of cardiovascular diseases.